Exploring the Potential Integration of Virtual Human-based Artificial Intelligence into the Marketing of Tourism Spots - Patak, Andi Anto; Yaumi, Muhammad Taufik Al Hakim; Yaumi, Muhammad (Tamaddun Life, 2025)
This study explores how virtual human-based artificial intelligence can be used to enhance the promotional strategies of tourism spots in Indonesia. As digital technologies rapidly evolve, these destinations need to adopt innovative solutions to enhance their appeal and sustainability. We examine the potential of integrating virtual human AI to enhance the image and promotion of these destinations on digital platforms, employing a qualitative approach. This involves analyzing case studies of several Indonesian tourism spots that have embraced digital technology for management and promotion. Data were gathered from various academic sources, including journals, research reports, and digital publications on digital technology in tourism. Our analysis highlights emerging trends, challenges, and opportunities for integrating virtual human AI into destination management and marketing. Virtual human AI can enhance visitor interactions by offering personalized and innovative experiences. It can also create compelling virtual representations, improve data management, and expedite decision-making in promotional strategies. Nonetheless, challenges such as infrastructure limitations and the need to raise awareness among tourism managers remain. This discussion offers valuable insights into how digital technology can help shape destination identity and attract more tourists, emphasizing the importance of building human resource capacity to make the most of these new tools. Ultimately, this research aims to serve as a helpful reference for developing technology-driven destination promotion in Indonesian tourism destinations.